An approach for enhancing heterologous production of Providencia rettgeri penicillin acylase in Escherichia coli - Chou, C. P.; Wang, W. C.; Lin, M. I. (Biotechnology Progress, 2000)
Heterologous production of Providencia rettgeri penicillin acylase (PAC) was optimized in Escherichia coli. Several factors, including carbon, temperature, and host effects, were identified to be critical for the enzyme overproduction. The optimum culture conditions for the enzyme production vary for different host/vector systems. With the optimization, both volumetric and specific PAC activities could be significantly improved by more than 50-fold compared to the native expression in P. rettgeri. The heterologous production could be possibly limited by translation or posttranslational steps, depending on the culture temperature and host/vector system. To our knowledge, this is the first evidence demonstrating the limiting step for the production of P. rettgeri PAC and the existence of the P, rettgeri PAC precursor.